The association between non-alcoholic fatty liver disease and atopic dermatitis: a population-based cohort study - Gau, Shuo-Yan; Huang, Ching-Hua; Yang, Yih; Tsai, Tung-Han; Huang, Kuang-Hua; Lee, Chien-Ying (Frontiers in Immunology, 2023)
Abstract Background: In previous studies, it was reported that NAFLD incidence and prevalence was increased in children atopic dermatitis patients. Nevertheless, the actual association between the two diseases has not been fully proved in large-scale studies and real-world evidences were missing. The objective of this nationwide, longitudinal cohort study was to evaluate the association between NAFLD and atopic dermatitis. Methods: The National Health Insurance Research Database in Taiwan was utilized in this study. Patients with records NAFLD diagnosis were recruited as experimental group and patients having less than three outpatient visits or one inpatient visiting record due to NAFLD were excluded from the study design. Non-NAFLD controls matched based on 1:4 propensity score matching. Potential confounders including age, gender, comorbidity and medical utilization status were considered as covariates. Risk of future atopic dermatitis would be evaluated based on multivariate Cox proportional hazard regression. Results: Comparing with people without NAFLD, decreased risk of atopic dermatitis in NALFD patients had been observed (aHR=0.93, 95% CI, 0.87-0.98). The trend was especially presented in young NAFLD patients. In patients younger than 40 years old, 20% decreased risk of atopic dermatitis was reported (aHR=0.80, 95% CI, 0.70-0.92). Conclusion: People with NAFLD were not associated with increased risk of atopic dermatitis. Conversely, a 0.93-fold risk was noted in NAFLD patients, comparing with NAFLD-free controls. Future studies were warranted to evaluate further mechanism regarding the interplay between the inflammatory mechanisms of NAFLD and atopic dermatitis.